Outcome of upper respiratory tract infections in healthy children: Antibiotic stewardship in treatment of acute upper respiratory tract infections: Outcome of upper respiratory tract infections in healthy children - Khan, Ejaz Ahmed; Raja, Mazhar Hussain; Chaudhry, Shehla; Zahra, Tehreem; Naeem, Salman; Anwar, Masuma (Pakistan Journal of Medical Sciences, 2020)
Objective: The objective of the study was to assess the outcome of upper respiratory tract infections (URTI) in healthy children. Methods: This descriptive study was conducted on 314 children aged 3-36 months in the paediatric outpatient clinic and emergency department with symptoms of URTI (fever, cough, rhinorrhoea) for ≤5 days. Patient’s demographics, clinical features, laboratory data and outcome were recorded. Follow up phone calls were made to parents on day 7 (response 93.6%) and day 14 (response 94.6%) to record outcome. Results: A total of 314 children with URTIs were included. Majority (57.6%) were males and <1year of age (40%). Common manifestations of URTI were fever (89%), cough (79%), rhinorrhoea (62%), pharyngitis (79%) and conjunctivitis (46%). More than half (53%) had history of contact with URTI in a family member. Mean duration of symptoms was 2.7±1.3 days. Majority (93%) of children were given supportive treatment and only 6.7% received antibiotics initially. Most of children (76%) recovered within one week and 91.8% within two weeks with supportive care only. Only 4% children were hospitalized and 12% required follow up visit of which 16% needed oral antibiotics. Complications or deaths did not occur. Conclusions: Majority of URTIs in healthy children resolved with supportive treatment and do not require antibiotics. Antibiotic stewardship in simple URTIs should be practiced using awareness and advocacy campaigns. doi: https://doi.org/10.12669/pjms.36.4.1420 How to cite this: Khan EA, Raja MH, Chaudhry S, Zahra T, Naeem S, Anwar M. Outcome of upper respiratory tract infections in healthy children: Antibiotic stewardship in treatment of acute upper respiratory tract infections. Pak J Med Sci. 2020;36(4):642-646. doi: https://doi.org/10.12669/pjms.36.4.1420 This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/3.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.